2014
DOI: 10.1002/ptr.5184
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Effects of Pycnogenol® on Oxidative Stress and DNA Damage Induced by Sepsis in Rats

Abstract: The aim of this study was to evaluate the protective effects of Pycnogenol® (Pyc), a complex plant extract from the bark of French maritime pine, on oxidative stress parameters (superoxide dismutase (SOD), and glutathione peroxidase (GPx) activities and total glutathione (GSH) and malondialdehyde (MDA) levels), an inflammatory cytokine (tumor necrosis factor alpha (TNF-α) level) and also DNA damage in Wistar albino rats. Rats were treated with 100 mg/kg intraperitonally Pyc following the induction of sepsis by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 56 publications
5
32
1
Order By: Relevance
“…The severity of tissue injury induced by sepsis is correlated with TNF-alpha level and there is a relation between inflammation and oxidative stress (26). In our study, as in our previous data (13)(14)(15), plasma TNF-alpha levels significantly increased in the septic rats, indicating an inflammatory response to sepsis. Single and double DNA strand breaks, base modifications, fragmentation of deoxyribose, formation of DNA-protein cross-links as well as abasic sites may occur as a result of oxidative DNA damage.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The severity of tissue injury induced by sepsis is correlated with TNF-alpha level and there is a relation between inflammation and oxidative stress (26). In our study, as in our previous data (13)(14)(15), plasma TNF-alpha levels significantly increased in the septic rats, indicating an inflammatory response to sepsis. Single and double DNA strand breaks, base modifications, fragmentation of deoxyribose, formation of DNA-protein cross-links as well as abasic sites may occur as a result of oxidative DNA damage.…”
Section: Discussionsupporting
confidence: 86%
“…The decreases in GSH and increases in MDA levels were determined in the hepatic and renal tissues of septic rats (25). In our study, as for our previous data (13)(14)(15), the increases in MDA levels and decreases in GSH levels and SOD and GPX activities in the liver and kidney were shown in the septic rats compared to the sham group.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In a study conducted on the efficacy of pycnogenol in wound healing in diabetic rats, it was reported that Pycnogenol is a feasible option to accelerate wound healing 23 . In a study using an experimental sepsis model in rats, it was reported that the production of free oxygen radicals in rats treated with Pycnogenol was significantly reduced 24 . In a study conducted in rats, it was reported that Pycnogenol facilitated the healing of colon anastomoses 25 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…The dose of PYC ® was selected according to our previous study. 18 After the end of this procedure, blood samples obtained through cardiac puncture were collected into preservative-free heparin tubes for the biochemical and the DNA damage evaluations.…”
Section: Experimental Protocolmentioning
confidence: 99%